Mechanisms of Selective Attention in Generalized Anxiety Disorder. (September 2015) - Yiend, Jenny; Mathews, Andrew; Burns, Tom; Dutton, Kevin; Fernández-Martín, Andrés; Georgiou, George A.; Luckie, Michael; Rose, Alexandra; Russo, Riccardo; Fox, Elaine
A well-established literature has identified different selective attentional orienting mechanisms underlying anxiety-related attentional bias, such as engagement and disengagement of attention. These mechanisms are thought to contribute to the onset and maintenance of anxiety disorders. However, conclusions to date have relied heavily on experimental work from subclinical samples. We therefore investigated individuals with diagnosed generalized anxiety disorder (GAD), healthy volunteers, and individuals with high trait anxiety (but not meeting GAD diagnostic criteria). Across two experiments we found faster disengagement from negative (angry and fearful) faces in GAD groups, an effect opposite to that expected on the basis of the subclinical literature. Together these data challenge current assumptions that we can generalize, to those with GAD, the pattern of selective attentional orienting to threat found in subclinical groups. We suggest a decisive two-stage experiment identifying stimuli of primary salience in GAD, then using these to reexamine orienting mechanisms across groups.